Sistem Informasi Pengelolaan Data Berbasis Website Pada DPP LSM KPK di Pekanbaru - Sugiyanti, Sugiyanti; Budi, Eko Setia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Non-Governmental Organization (NGO) is one of the non-profit institutions in Indonesia, one of which is in the city of Pekanbaru, namely the Central Leadership Council of the Corruption Eradication Community Non-Governmental Organization (CLC CEC NGO). The data management information system at the CLC CEC NGO still uses a simple system, which consists of financial data management, meeting decision data management, correspondence data management, data management findings from both the CLC CEC NGO and from each Regional Leadership Council, Region Leadership , and Branch Leadership Council, agenda data management, and information data management. Data management is still simple, there are often problems encountered such as loss of documents, the preparation of documents that are not organized so that it is difficult to find them and requires a lot of time, also repeated data recording. The problems faced can be solved by building a website-based data management information system. The purpose of making this data management information system is to provide convenience in data management at the CLC CEC NGO. The method that the author uses in making this data management system is to use the waterfall method, while making this website, the author uses the CodeIgniter framework and bootstrap. For website testing, the author uses Black Box Testing. With this data management website, it is hoped that it will provide convenience in data management for the CLC CEC NGO